1997
DOI: 10.1016/s0092-8674(00)80491-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of a Functional Drosophila Centromere

Abstract: Centromeres play a critical role in chromosome inheritance but are among the most difficult genomic components to analyze in multicellular eukaryotes. Here, we present a highly detailed molecular structure of a functional centromere in a multicellular organism. The centromere of the Drosophila minichromosome Dp1187 is contained within a 420 kb region of centric heterochromatin. We have used a new approach to characterize the detailed structure of this centromere and found that it is primarily composed of satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
202
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(214 citation statements)
references
References 77 publications
(115 reference statements)
10
202
1
1
Order By: Relevance
“…D. melanogaster transposon BEL has been found in the functional 420-kb Drosophila minichromosome centromere. The transposon BEL is one of the five conserved, intact and complete transposons inserted directly into the AATAT array of this functional centromere (Sun et al, 1997). The fly C. capitata also showed interspersed TEs in satDNA (Stratikopoulos et al, 2002), some of which was highly conserved and showed a significant similarity with transposon BEL.…”
Section: And References Therein)mentioning
confidence: 99%
See 1 more Smart Citation
“…D. melanogaster transposon BEL has been found in the functional 420-kb Drosophila minichromosome centromere. The transposon BEL is one of the five conserved, intact and complete transposons inserted directly into the AATAT array of this functional centromere (Sun et al, 1997). The fly C. capitata also showed interspersed TEs in satDNA (Stratikopoulos et al, 2002), some of which was highly conserved and showed a significant similarity with transposon BEL.…”
Section: And References Therein)mentioning
confidence: 99%
“…The fly C. capitata also showed interspersed TEs in satDNA (Stratikopoulos et al, 2002), some of which was highly conserved and showed a significant similarity with transposon BEL. However, it is not known whether this conservation, even in different organisms, is due to a recent insertion or it is a consequence of a selective or functional constraint probably related to centromere activity (Sun et al, 1997;Stratikopoulos et al, 2002).…”
Section: And References Therein)mentioning
confidence: 99%
“…Centromeric satellites serve as the core of the centromere, which is flanked by pericentric heterochromatin rich in middle repetitive elements, including retroelements and transposons. Because of the abundance of various repeats, centromeres of most eukaryotic chromosomes are upward of 1 Mb in size, mostly devoid of genes, and their sequencing and assembly pose a big challenge (Su et al 1997;Hosouchi et al 2002). Among the sequenced genomes of many multicellular eukaryotes, including Drosophila melanogaster, human, mouse, Arabidopsis thaliana, and rice, only the centromeres of rice chromosomes 3, 4, 5, and 8 have been fully assembled Wu et al 2004;Y.…”
Section: Entromeres and Their Associated Kinetochoresmentioning
confidence: 99%
“…In the Drosophila melanogaster genome, each centromeric region seems to contain different sets of satellite DNA sequences (Abad et al 1992(Abad et al , 2000Lohe et al 1993;Sun et al 1997;Agudo et al 1999;Lamb and Birchler 2003). The X chromosome contains a large block of complex 1.688 satellite DNA (359-bp repeat unit), located in the centromeric region and in the adjacent 1 pericentromeric heterochromatin (Lohe et al 1993;Abad et al 2000) (Figure 1A), and large autosomes contain arrays of different subfamilies of 1.688 satellite DNA in the pericentromeric heterochromatin.…”
mentioning
confidence: 99%